Validação da via de biossíntese de selenocisteína e selenoproteínas em Trypanosoma por RNA de interferência - Costa, Fernanda Cristina (2012)
Selenium (Se) is an essential element found in selenoproteins as the 21st amino acid (Selenocysteine Sec).For the Sec incorporation and the related biosynthetic pathaway, several elements are required: tRNASec, a UGA codon and a Sec insertion sequence (SECIS), a conserved motif downstream of the selenoprotein encoding gene. Selenoproteins generally participate in the cellular redox balance, playing an important role on cell growth and proliferation. These proteins, as well as the the Sec synthesis pathway, are present in members of the Bacteria, Archaea and Eukarya domains, being identified in several protozoa, including the kinetoplastids. Auranofin, a gold-contaning antirheumatic drug, is a known selenoproteins inhibitorand Trypanosoma brucei and Leishmania majorcells are sensitive to this compound, with a LD50 in nanomolar range. This indicates a possible dependence of these parasites on selenoproteins. Theselenophosphate synthetase (SELD/SPS2) is responsible for the formation of monoselenophosphate from selenide and ATP, being essencial for selenoprotein biosynthesis. SPS2 knockdown led to apoptosis under sub-optimal growth conditions. The selenoproteome of these flagellated protozoa consists of distant homologs of the mammalian SelK and SelT, and a novel selenoprotein designated SelTryp, a kinetoplastidspecific protein. The functions of any of these selenoproteins are not known.We have investigated the effect of their downregulation in T. brucei to interpret their possible physiological role. The TbSelK depletion shows no effect on growth under optimal conditions, but the cells became more sensitive to endoplasmic reticulum stress agents and oxidative stress, suggesting that SelK is an ER stress-regulated protein and plays an important role in protecting T. brucei cells from ER stress agent. The TbSelT gene silence by RNA interference hampers the parasite survival, but the sensitivity to the agents tested was not asevident as it was forTbSelK, suggesting a role for TbSelT in protection against stress, but not specifically ER stress. Our results show the importance of selenocysteine and selenoproteins to parasite survival.